Appoaches to the principle of State economic subsisiarity over the last 25 years - Rodríguez Cairo, Vladimir (2020)
Objective: The research described the characteristics of the main approaches to the State's principle of economic subsidiarity over the last twenty-five years. Method: Articles published in indexed scientific journals with a descriptive method were analyzed, using inclusion and exclusion criteria. Results: It was obtained as a result of nineteen articles whose main approaches are: vertical/horizontal and positive/negative. Conclusions: It was concluded that, while the golden rule must be free private initiative or economic freedom, the subsidiary role of the state in the economy, is based on the agents who exchange in the markets supports on the insufficient rules to achieve well-being.